The Marikina Municipal Library an evaluation with implications on collection development - Basa, Jocelyn P. (1995)
Libraries were established to provide as many people as possible with the reading material that is appropriate for recreational, informational, and educational needs. Since its conception in August 11, 1956, the Marikina Municipal Library has grown from its previous small space in the Municipal Session Hall to its present location above the Philippine National Bank, Marikina Branch. The purpose of this study was to evaluate its book, periodical, audio-visual, and other non-book collection, and to find the strengths and weaknesses of its collection in meeting the goals of the library. The hypotheses of this are : 1) The library collection is not able to support the information needs of the clients; 2) The users, especially the younger ones, do not fully utilize the facilities of the library; 3) The patrons seldom use the reference materials; and 4) The patrons go there for recreation. The research used are the interview, document analysis, and the questionnaire. The simple random sampling was used for the respondents to the questionnaires.